(untitled) (Journal of Educational Sciences, 2025)
One of the factors affecting students’ academic performance is their perception of the meaning of the term not by heart, but by understanding it, the assimilation by students of the simultaneous use of the same term in several subject areas. With the help of the term, we form students’ scientific knowledge about being. Therefore, the definition of the term should be easy for students to perceive in order to remain in their memory for a long time. To do this, subject teachers should be able to justify the ways of creating subject terms studied in the humanities and natural sciences. The terminologist should be able to fully explain the sequence of terminologization of vocabulary sources. Only then will the term retain its stability. Therefore, today’s requirement is to ensure the full mastery of the meaning of the term by the student, its long-term retention in the language consciousness (memory) of the student, as well as to ensure the integrative thinking of the student. Therefore, consideration of the terminological meaning of the word and methods of its integrated learning is the main goal of this article. In accordance with this goal, a theoretical and practical review of the work of foreign, Soviet and Kazakh scientists and teachers on integrated learning is made. The advantages of integrated learning in the educational process and its effectiveness in improving the learning and cognitive ability of students are considered. The issues of accumulation of the knowledge base, systematization of industry information, the formation of application skills, analysis, synthesis by combining theoretical and practical knowledge obtained in the student’s mind are analyzed. The problem of teaching the meaning of the term on the basis of integrated learning is explained. It has been scientifically proven that one term can be used in the terminological system of several subjects (geography, biology, Kazakh language, etc.). 55 schoolchildren took part in the practical part of the study. Methods of assimilation of the meaning of the term corresponding to each subject are proposed. Key words: terms, pedagogical technology, integrated learning, transubject, metalanguage.